'Warming' global information systems to promote competitiveness in the era of climate change. (1st January 2015) - Gasmelseid, Tgelsir Mohamd
The factors that drive the international economic system are changing in scale and magnitude in a way that affects the competitiveness of multi–national organisations. In addition to the internal complexities, the competitiveness of many sectors is being challenged with external transformations (such as climate change) that affect policy formulation and resource utilisation. However, the examination of the impacts of climate change continued to be approached through the use of microeconomic analysis that focus on analysing the impact of carbon trading strategies on productivity and profitability in certain sectors such as energy. Such analysis (despite its importance) seems to be of a limited focus to provide a clear understanding and guidelines for large scale interventions and innovations required to create and maintain competitiveness in the era of climate change. This paper examined the context of competitiveness in the era of climate change using a decision–making oriented approach with emphasis on the impacts of climate change on competitiveness and information systems. The paper examined the potential information system 'overheating' concerns and recommended some 'warming' measures.